Interaction Effect of Applied Calcium and Magnesium on Alfisols of Karnataka and its Influence on Uptake and Yield Levels of Tomato (Solanum lycopersium L.) - B L Kasinath (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2014)
In a field experiment, interaction effects of applied Ca, Mg and K on yield and quality of tomato and soil nutrient levels was studied in Alfisols of Karnataka. The results showed application of Mg enhanced fruit yield up to 100 kg Mg ha-1 and decreased at higher levels of Mg. The application of Ca also enhanced the yield of tomato but their combined application at different levels had negative effect of one on the other. The results indicated that optimum combination of Mg and Ca was 100 and 250 kg ha-1 respectively for obtaining higher yield in tomato. Soil P content enhanced with application of both Ca and Mg. However, applied Ca and Mg showed significant negative effect on both soil and K content. Interaction effect was however, non-significant on soil pH, EC, OC and Soil N content.